Psychological and Cognitive Developments among Adolescents - a Longitudinal Study- - Fuad Mohammed Frieh; Asmaa H. Abdulsatar (مجلة جامعة الأنبار للعلوم الإنسانية, 2022)
Developmental changes are a successive series of changes that aim to complete the maturity of the human beings from the physical, mental, psychological and emotional aspects. These changes occur in a specific order and in a predictable way as a result of maturity and experience. To achieve the aim of the research, a main question was created: what is the level of the developmental changes among adolescents? Is there a relationship between the psychological and cognitive developments? Is the degree of changes differ according to sex and age? Accordingly, the current research aimed to identify the level of developmental changes among adolescents and the differences between developmental changes according to some demographic variables (sex - age). To achieve the aims of the research, (264) secondary school students were chosen from four schools. The age of the participants was between (14-17) years. To measure the developmental changes, the Rehacom system was adopted. After the analysis, the results of the current research showed that the level of developmental changes was high and statistically significant.